DATA MANAGEMENT SEBAGAI KUNCI KEUNGGULAN KOMPETITIF PERUSAHAAN DI ERA DIGITAL - Fitri Nabila Hasibuan; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2025)
With the rapid digital transformation, data has become a strategic asset that impacts every aspect of a company’s operations and decision-making. Although data is available in large quantities and from a variety of sources, the main challenge facing many companies is how to effectively manage data so that it can be used to create added value and competitive advantage. Data management, which encompasses a set of practices and policies to ensure the quality, integration, and security of data, has proven to be a key component in achieving these goals. This article takes a deep dive into the role of data management in improving the quality of data used for data-driven decision making. A good data management process not only ensures that data is accurate, reliable, and timely, but also ensures that it can be accessed, analyzed, and translated into insights that support innovation and business strategy.Through a holistic approach, this article identifies various important elements in data management, including data governance, data quality, data integration, and data security, which contribute to the creation of a company's competitive advantage. Data governance plays a role in setting rules and responsibilities related to data management, while data quality ensures that data used in analysis and decision making is not only accurate but also consistent and relevant. On the other hand, data security management is essential to protect sensitive data from potential leaks or misuse, which can damage reputation and consumer trust. Effective data management implementation can reduce operational costs, increase efficiency, and optimize resource use. In addition, companies can identify market opportunities faster, adjust strategies more dynamically with changing trends, and improve customer interactions and experiences through more personalized and responsive services. Thus, data management is not just a technical function, but more than that, it is a strategic element that is the foundation for a company's success and competitiveness.